Branded Pop: The Medium is the (Brand) Message - Bambang Sukma Wijaya (I-Pop: International Journal of Indonesian Popular Culture and Communication, 2020)
Amidst high consumer skepticism regarding conventional promotions and advertisements, contemporary branding techniques continue to evolve. Brands are now actively creating pop culture works that implicitly embed brand narratives, content, and discourse into various media, ranging from dramas, films, music, and performance art to games and installations. Through the strategy and concept of "Branded Pop," these creative works tell stories without appearing to "sell" or "advertise." The brand message becomes an integral part of the work itself, allowing audiences to fully enjoy the pop culture content without the disruption of sponsored messages or product insertions that feel persuasive or forced. Employing a narrative interpretive review method, this article analyzes and synthesizes relevant strategies based on extensive literature, covering branded entertainment, branded content, brand placement, product placement, creative publicity, creative branding, creative media advertising, ambient media/advertising/communication, guerrilla marketing/advertising, arts marketing, cultural branding, emotional branding, brand narratives, brand storytelling, and Branded Pop Theory. This study offers implications for future branding strategy innovations that precisely integrate pop culture and brand messages, allowing the message to merge with the medium and successfully become part of consumers' daily lives. As a pioneering academic study, this article contributes significantly to enriching the theoretical landscape at the intersection of branding, communication/media studies, and cultural studies.